Development of a patient reported outcome instrument for chronic sialadenitis - Fatemeh Ramazani; Amr Hamour; Caroline C. Jeffery; Vincent Biron; Yaser Alrajhi; Daniel O’Connell; David W. J. Côté (Journal of Otolaryngology - Head and Neck Surgery)
Abstract Background Sialendoscopy assisted treatments are a minimally invasive management modality for chronic sialadenitis. Clinicians report improved patient quality of life (QoL) following sialendoscopy assisted treatments, but there exist gaps in current literature about patient reported outcomes (PROs). PROs are outcome measures developed based on patient perceptions. Objective The objective of this study was to create a PRO instrument for chronic sialadenitis, to assess the efficacy of sialendoscopy assisted treatments in improve patients’ QoL. Design This four-phase qualitative study employed grounded theory methodology and a modified Delphi technique. In Phase I, ten patients were interviewed to identify the QoL domains impacted by chronic sialadenitis. In Phase II, these QoL domains were presented to a focus group of different chronic sialadenitis patients, who were asked to rank them by order of importance. A conceptual framework of QoL domains impacted by chronic sialadenitis was created based on patient consensus. Itemization of the PRO questionnaire was done by a focus group of four Otolaryngologists in phase III. Lastly, the questionnaire was completed in Phase IV by cognitive interviewing of five new chronic sialadenitis patients; ensuring ease of understanding and clarity. Results Patients identified 15 domains of QoL impacted by chronic sialadenitis, divided into three sub-scales: physical symptoms, psychosocial symptoms, and activity restriction. These domains provided the basis for creation of a 22-item PRO questionnaire, with a Likert-type response scale. Conclusion Clinical application of the novel questionnaire produced by this study will allow for a patient-centered assessment of the patient reported effectiveness of sialendoscopy assisted therapies for management of chronic sialadenitis. Level of evidence Level V. Graphical Abstract